Combination of sodium-glucose cotransporter 2 inhibitor and dipeptidyl peptidase-4 inhibitor in type 2 diabetes: a systematic review with meta-analysis - Min, Se Hee (Sci Rep, 2018)
Sodium glucose cotransporter 2 (SGLT2) inhibitors and dipeptidyl peptidase-4 (DPP4) inhibitors have complementary mode of action. For the meta-analysis comparing the efficacy and safety between SGLT2 inhibitor plus DPP4 inhibitor (SGLT2i/DPP4i) and placebo plus DPP4 inhibitor (PCB/DPP4i) in patients with type 2 diabetes mellitus (T2DM), we selected randomized controlled trials from electronic databases by predefined criteria. The primary outcome of interest was the change in glycated hemoglobin A1c (HbA1c) from baseline. Of 605 potentially relevant studies, 7 eligible RCTs comprising 2,082 patients were included.SGLT2i/DPP4i showed a greater reduction in HbA1c (weighted mean difference −0.6%, 95% CI −0.7 to −0.5%), fasting plasma glucose, 2 h postprandial plasma glucose, and body weight compared to PCB/DPP4i. The risk of hypoglycemia increased in SGLT2i/DPP4i compared to that in PCB/DPP4i only when insulin or sulfonylureas were included as a background therapy. The risk of urinary tract infection was not increased in SGLT2i/DPP4i; however, the risk of genital infection increased upon adding SGLT2 inhibitors to pre-existing DPP4 inhibitors. In conclusion, compared to PCB/DPP4i, SGLT2i/DPP4i achieved better glycemic control and greater weight reduction without increasing the risk of hypoglycemia and urinary tract infection in patients with inadequately controlled T2DM.